Pengaruh Kepemimpinan dan Kedisiplinan Karyawan terhadap Kinerja Karyawan - Nuraini, Nuraini; Indiyati, Dian (Jurnal Ilmu Manajemen, 2023)
Company with one of the plantation units that contributes to improving the output and processing of oil palm plantations is PT Perkebunan Nusantara V Sei Garo. The corporation is aware of how critical it is to assess the caliber of its human resources, in particular, the leadership and attitude of discipline inside the organization. The purpose of this study is to ascertain the link and the interdependence of leadership, employee discipline, and employee performance at PT Perkebunan Nusantara V Kebun Sei Garo. This study employs a quantitative methodology with a path analysis approach. Purposive sampling was the method of choice for the sample of 175 PT Perkebunan Nusantara V Kebun Sei Garo personnel. The study's outcomes demonstrate leadership and employee discipline have a moderately positive impact on employee performance. According to the findings of the path analysis, leadership, and discipline have a combined 49.8% effect on employee performance, with the remaining 50.2% being influenced by other factors that were not studied. The conclusion is that at PT Perkebunan Nusantara V Kebun Sei Garo, employee leadership and discipline may have a major positive impact on worker performance. The researcher's recommendation is that, in light of the study's findings, you can manage better to improve the flaws that already exist in the organization by fostering a better work environment and adhering to rules set forth by the company policy.